Environmental factors associated with non-infective acute respiratory illness in athletes: A systematic review by a subgroup of the IOC consensus group on "acute respiratory illness in the athlete". Issue 6 (June 2022) - Bougault, Valérie; Adami, Paolo Emilio; Sewry, Nicola; Fitch, Ken; Carlsten, Christopher; Villiger, Beat; Schwellnus, Martin; Schobersberger, Wolfgang
Abstract: Objectives: The aim of this study is to review the evidence available suggesting that environmental conditions represent a risk factor associated with non-infective acute respiratory illness in athletes. Design: Systematic review. Methods: PubMed, EBSCOhost and Web of Science (1st January 1990–31 July 2020) were searched systematically using keywords related to male and female athletes (i.e. from physically active individuals to elite athletes), aged 15–65 years and a combination of the terms (non-infective acute respiratory illness AND [pollution OR allergies OR climate] AND athletes AND prevalence/incidence/risk factors). Results: A total of seven papers (n = 1567 athletes) addressed our question. Among these, one focused on indoor air pollution, four on chlorinated swimming pool exposure and two on cold air conditions. None was selected for allergies, outdoor air pollution or other climatic conditions. Except rhinitis induced by swimming in chlorinated pools (n = 1), no respiratory disease due to the environment was identified specifically in athletes. The levels of chloramines in swimming pools (n = 2) and air pollutant in arenas (n = 1) were identified as risk factors for rhinitis and respiratory symptoms when exercising. Discussions: There is a paucity of data on the prevalence, incidence and risk factors of being acutely exposed to chlorine by-products, air pollution, cold air or altitude on the development of respiratory disease specifically in athletes. Noting the lack of a clear definition of environmentally induced lung disease in athletes, distinct from that of the general population, we addressed the few published management plans to protect athletes' airways for each specific environment.